Der Name des Kronprinzen Taharqas - Meyrat, Pierre (Zeitschrift für ägyptische Sprache und Altertumskunde, 2012)
New interpretation of the name of Taharqa’s heir apparent Ušanahuru , only known from two monuments of Esarhaddon. The usually accepted hypothesis is discussed and rejected as unlikely, according to the rules of transcription of Egyptian into Neo-Assyrian cuneiform. A new name seems more convincing, but it never occurs in hieroglyphic sources. Another option is then considered, namely that of a Meroitic origin.